In vitro effects of different innate-immune stimulants on Chinook salmon embryo cell line (CHSE-214): transcriptional and translational studies - Estévez Estévez, Rosana A., 1977- (2015)
The innate immune response in fish is of particular relevance for infections as it forms the first line of defense against bacteria and viruses. Antibiotics and vaccination are the most common method used to control the infectious diseases in aquaculture. The disadvantages with these approaches are the selection of resistant bacteria and poor protection. Defining inducers for the innate immunity in fish could provide alternative approach against infections. The expression of innate effectors: cathelicidin, hepcidin, iNOS, MDA5, RIG-I and ISG25 mRNA was assessed by qPCR in Chinook salmon cell line (CHSE-214) before and after treatment with potential inducers: ß-hydroxy-ß-methylbutyrate, 4-phenylbutyrate, 1,25(OH)2 D3, omega-3 and omega-3 ethyl ester from fish oil and cod liver oil. Cathelicidin was found to be up-regulated by all the inducers, while the other innate immune effectors were found up-regulated by specific inducers. Antimicrobial activity was also measured and indicated enhancement at the protein level. In addition, we tried to acquire an antibody for Atlantic salmon cathelicidin by immunization of rabbit with synthetic peptides derived from cathelicidin. Specific cathelicidin antibodies were not obtained in this experiment. The findings might contribute to the development of alternatives to the classical prophylactic methods, antibiotics and vaccination in aquaculture improving the fish immune response and consequently the health of fish in aquaculture.